2018
DOI: 10.2147/ahmt.s135423
|View full text |Cite
|
Sign up to set email alerts
|

Gambling disorder in adolescents: prevalence, new developments, and treatment challenges

Abstract: Research on adolescence gambling over the past twenty years has revealed significant incidence and prevalence rates and highlighted the possible negative effects on an adolescent’s well-being. Several risk and protective factors have also been identified. Over the course of the past few years, technological advances have heralded the advent of new avenues for gambling as well as new opportunities to gamble without any direct monetary exchange. This review article examines those established trends as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 67 publications
(61 reference statements)
2
26
0
4
Order By: Relevance
“…Generally, the correlates of problem gambling found in this study (sexual abuse victimisation, weekly alcohol use, male gender, breakup, bullying victimisation, being in a romantic relationship, parental divorce and being in a polygamous family) are consistent with evidence in the global literature (Derevensky et al 2011;Floros 2018;Grande-Gosende et al 2020;Hayer and Griffiths 2015;Lane et al 2016;Molinaro et al 2014;Shead et al 2011). Specifically, this study shows that regardless of gender, participants who reported sexual abuse victimisation were about three times more likely to experience problem gambling.…”
Section: Factors Associated With Problem Gamblingsupporting
confidence: 90%
“…Generally, the correlates of problem gambling found in this study (sexual abuse victimisation, weekly alcohol use, male gender, breakup, bullying victimisation, being in a romantic relationship, parental divorce and being in a polygamous family) are consistent with evidence in the global literature (Derevensky et al 2011;Floros 2018;Grande-Gosende et al 2020;Hayer and Griffiths 2015;Lane et al 2016;Molinaro et al 2014;Shead et al 2011). Specifically, this study shows that regardless of gender, participants who reported sexual abuse victimisation were about three times more likely to experience problem gambling.…”
Section: Factors Associated With Problem Gamblingsupporting
confidence: 90%
“…Research generally supports the concept of migration to monetary gambling, particularly in young people [80][81][82][83][84][85][86][87][88]. Micro-transactions within simulated gambling were identified as a potential predictor of migration [88].…”
Section: Video Gaming and Gamblingmentioning
confidence: 67%
“…Internationally, adolescent gambling is investigated in numerous papers (for reviews see Blinn-Pike et al 2010;Calado et al 2017) and research has grown considerably over the past two decades (Derevensky and Gilbeau 2015). Research has tended to be quantitative, focusing on the prevalence, correlates and risk factors of gambling (Blinn-Pike et al 2010;Floros 2018). Rarely, attention has been devoted to the time trends of gambling among the adolescent population (Jacobs 2000;Stinchfield 2011).…”
Section: Introductionmentioning
confidence: 99%